Designing CA/CM to fit not-for-profit organizations. Issue 1 (4th January 2016) - Appelbaum, Deniz; Kozlowski, Stephen; Vasarhelyi, Miklos A.; White, Joel
Abstract : Purpose: – The purpose of this project is to undertake continuous auditing and monitoring (CA/CM) implementations working with small-to-medium-sized (SME) not-for-profit (NFP) organizations of varying sizes, business purposes and levels of technical sophistication. Design/methodology/approach: – This paper discusses a project using a case study approach with an SME NFP entity. Findings: – The findings support the discussions in the literature regarding CA/CM adoption in organizations, particularly regarding its implementation benefits and challenges. Research limitations/implications: – The project is not complete in that additional case studies could possibly offer additional applicability to the findings. Practical implications: – This case study illustrates the issues inherent with the process of adopting new technologies. It provides insights for others considering adoption of CA/CM tools or protocols. Social implications: – The need for more reliable auditing has never been more urgent than it is today in the NFP environment, and this case study demonstrates how an NFP could address these critical needs of increased reporting accountability and internal controls. Originality/value: – The application of CA/CM is quite interesting and relevant in this modern real-time economy. This case study provides a new area of research in the field of CA/CM and, as such, contributes to the literature.